CULTURAL VALUES REPRESENTED IN THE METATAH (TOOTH FILING) RITUAL: AN ETHNOPHOTOGRAPHIC PERSPECTIVE - Raden Daniel Wisnu Wardana; Dwi Kartikawati; Yuri Alfrin Aladdin (Universitas Nasional, 2025)
The Metatah ceremony, also known as tooth cutting, is a significant event in Balinese society, imbued with intellectual and spiritual significance. This study seeks to elucidate the portrayal of cultural values in the Metatah ceremonial utilizing an ethnophotographic methodology. This study use qualitative methodologies and visual ethnographic analysis to examine the manifestation of cultural meanings within the visual components of the Metatah ceremonial. This study demonstrates that ethnophotography effectively depicts the sacred and transformational aspects of the Metatah ceremony, while also functioning as a viable medium for cultural preservation. This collection of images of the traditional ceremonial illustrates several narratives within Balinese culture, characterized by simplicity yet rich in both explicit and implicit connotations. These discoveries significantly enhance the field of visual anthropology, particularly in relation to coming-of-age rites in Bali